Prova estética e funcional: uma decisão em conjunto - Goiato, Marcelo Coelho [UNESP]; Nobrega, Adhara Smith [UNESP]; Gennari Filho, Humberto [UNESP]; dos Santos, Daniela Micheline [UNESP] (My University, 2014)
An important phase of rehabilitation treatment, is the aesthetic and functional testing, performed with the patient. Its relevance is because at this time it’s possible to have a very faithful preview of the final result of the prosthesis, but, if necessary, still allow changes. Therefore, the objective of this review is to describe didactically the clinical steps and factors that should be examined by the dentist at the moment of aesthetic and functional testing of a complete denture. This clinical stage basically involves four requirements to be analyzed: mechanical, functional, aesthetic and phonetic. After the jointly analysis with all the requirements, the patient must approve, preferably in writing, the completion of the prosthesis. In case of need for any changes, this is when it should be performed, followed by new aesthetic and functional testing. It should be noted that the patient’s opinion is always sovereign in deciding to end the denture.

Uma importante fase do tratamento reabilitador, constitui a prova estética e funcional, realizada juntamente com o paciente. A sua relevância é porque nesse momento é possível ter uma prévia muito fiel do resultado final da prótese, mas que ainda permite alterações. Assim, o objetivo dessa revisão é descrever didaticamente os passos clínicos, bem como os fatores que devem ser analisados pelo cirurgião-dentista, no momento da prova estética e funcional de uma prótese total. Esta etapa clínica envolve basicamente quatro requisitos a serem analisados: mecânicos, funcionais, estéticos e fonéticos. Após a análise em conjunto de todos os requisitos, o paciente deve aprovar, preferencialmente por escrito, a finalização das próteses. Em caso de constatação de necessidade de alguma alteração, é nesse momento que deve ser realizada, seguida de nova prova estética e funcional. É necessário salientar que a opinião do paciente é sempre soberana na decisão de finalizar a prótese total.
Aesthetics and functional testing: a jointly decision
Keywords: Denture; Complete; Esthetics, Dental; Phonetics; Prótese total; Estética dentária; Fonética